Menumbuhkan Karakter Wirausaha Melalui Kegiatan Enterpreneur Day - Muhamad Safiul Umam (EXERO : Journal of Research in Business and Economics, 2021)
Entrepreneur day activities are the concept of activities in growing entrepreneurial character with the concept of learning to plan, produce and marketing processes in the school environment. Entrepreneur day activity is interesting to study because it is an activity program at SMP Islam Al Azhar 14 Semarang when the author was on duty in 2016. The research was carried out aimed at getting a picture of entrepreneurial character that can be grown through the implementation of entrepreneurial day activities. The research approach used is descriptive qualitative, the method used is interviews, observation, and documentation with triangulation as a data analysis technique. The results showed that of the 11 character indicators to be achieved, only five (5) characters could be grown, namely: (1) having a positive attitude, (2) working together, (3) leadership, (4) independence, and (5) being able to face challenges. problems, with the percentage of success indicators reaching 45.4%.